2013
DOI: 10.1097/igc.0b013e3182a16c93
|View full text |Cite
|
Sign up to set email alerts
|

Lymphovascular Space Invasion (LVSI) Is an Isolated Poor Prognostic Factor for Recurrence and Survival Among Women With Intermediate- to High-Risk Early-Stage Endometrioid Endometrial Cancer

Abstract: In our study, LVSI is the only significant and consistent poor prognostic factor for all the outcomes studied: recurrences and survival. Lymphovascular space invasion seems to be a better predictor than the other risk factors. This suggests a potential role for adjuvant systemic therapies in patients with LVSI, even in the absence of other high-risk features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
34
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 20 publications
5
34
0
2
Order By: Relevance
“…Other studies have shown a significant difference in the incidence of disease recurrence in patients with LVSI. 6,8 A previous study showed that among patients with recurrence of endometrial cancer, the rate of LVSI ranged from 28.3% to 54%, whereas among patients without recurrence, the rate of LVSI ranged from 10% to 12.6%. 6 In addition, patients with LVSI may present with more distant recurrences 8 and shorter median time from diagnosis to recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown a significant difference in the incidence of disease recurrence in patients with LVSI. 6,8 A previous study showed that among patients with recurrence of endometrial cancer, the rate of LVSI ranged from 28.3% to 54%, whereas among patients without recurrence, the rate of LVSI ranged from 10% to 12.6%. 6 In addition, patients with LVSI may present with more distant recurrences 8 and shorter median time from diagnosis to recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Tumors that are LVSI positive are classified as intermediate risk, and adjuvant treatment is recommended for these patients. 5,6 However, recent studies have shown that positivity for LVSI is the strongest prognostic factor for recurrence or cancer-related death 7,8 ; hence, LVSI has been the focus of increased investigation.…”
mentioning
confidence: 99%
“…22 Given the high recurrence rate in low-risk patients, this suggests a potential role for adjuvancy in positive LVSI, even without other high-risk features. 20,31,35 In Aristizabal et al 36 study, the survival difference and 5-year OS between stage I patients with positive LVSI and those with negative LVSI were highly significant (81% and 97%, P = 0.009), instead of differentiating by MI. According to these data, a stratification of the FIGO stage I based on the LVSI status would predict mortality better.…”
Section: Discussionmentioning
confidence: 92%